1991
DOI: 10.1063/1.350074
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic and crystallographic properties of novel Fe-rich rare-earth nitrides of the type RTiFe11N1−δ (invited)

Abstract: We succeed in inserting a number of nitrogen atoms into the RTiFe11 intermetallics. The nitrides retain the ThMn12-type structure, but with an increase in the unit cell volume. The crystallographic sites located by nitrogen atoms are determined by using neutron diffraction techniques. The nitrogen atoms are found to have an effect of increasing Curie temperature and saturation magnetization. Moreover, an essential change in magnetocrystalline anisotropy is observed upon nitrogenation. By all of these effects, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
29
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(29 citation statements)
references
References 7 publications
0
29
0
Order By: Relevance
“…The total magnetic moments of NdFe 11 Co and their nitrogenated compounds have almost the same values as those of NdFe 12 and its nitrogenated compound, and have much larger values than those of NdFe 11 Ti(8i), which are previously studied in theories and experiments. 1,2,11,12,32 Next the values of r …”
Section: Calculation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The total magnetic moments of NdFe 11 Co and their nitrogenated compounds have almost the same values as those of NdFe 12 and its nitrogenated compound, and have much larger values than those of NdFe 11 Ti(8i), which are previously studied in theories and experiments. 1,2,11,12,32 Next the values of r …”
Section: Calculation Methodsmentioning
confidence: 99%
“…Using first-principles method, we study the effect of substitutional 3d transition metal elements to the mother compound NdFe 12 . We find that Co has positive effect on the stability of the ThMn 12 structure.…”
mentioning
confidence: 99%
“…This phase can be stabilized by replacing some of the iron atoms with a small amount of other elements such as Ti, V, Mn, Co, Mo, Nb, Si, and Al, etc., and the RFe 12−x M x metallic compounds can be obtained. Some of the compounds of the type RFe 12−x M x are characterized by fairly high values of the Curie temperature, saturation magnetization and magnetocrystalline anisotropy [1][2][3][4]. So the iron-rich rare earth transition-metal compounds become new potential candidates for permanent magnet applications, and the study of these compounds is attracted intensively worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…PACS numbers: 75.50.Bb, 75.10.Lp It has been reported that the magnetic properties of iron-rich rare-earth intermetallic compounds with ThMn12 structure can be drastically changed upon nitrogenation or carbonation by gas-solid reaction which introduce carbon into the interstitial 2(b)-(0, 0, 2) site [1,2].…”
mentioning
confidence: 99%
“…In spite of carbides' unit volume decrease enhancement of magnetization and Curie temperature were obtained. Results are in quantitative agreement with experimental data.PACS numbers: 75.50.Bb, 75.10.Lp It has been reported that the magnetic properties of iron-rich rare-earth intermetallic compounds with ThMn12 structure can be drastically changed upon nitrogenation or carbonation by gas-solid reaction which introduce carbon into the interstitial 2(b)-(0, 0, 2) site [1,2].Recently it has been shown that some amount of carbon can be introduced into 1:12 intermetallics by arc-melting method, and the results of crystallographic and magnetic investigations of these compounds indicated that the effect of carbonation can be different from that observed in samples prepared by gas-solid method. The unit volume is observed to reduce slightly upon carbonation, and despite the unit volume reduction, saturation magnetization and Curie temperature increase significantly [3,4].…”
mentioning
confidence: 99%